Comparison of the In vitro Activity of Five Antimicrobial Drugs against Staphylococcus pseudintermedius and Staphylococcus aureus Biofilms - Ferran, Aude A.; Liu, JingJing; Toutain, Pierre-Louis; Bousquet-Mélou, Alain (Frontiers in Microbiology, 2016)
Resistance in canine pathogenic staphylococci is necessitating re-evaluation of the current antimicrobial treatments especially for biofilm-associated infections. Long, repeated treatments are often required to control such infections due to the tolerance of bacteria within the biofilm. To comply with the goal of better antibiotic stewardship in veterinary medicine, the efficacies of the available drugs need to be directly assessed on bacterial biofilms. We compared the activities of amoxicillin, cefalexin, clindamycin, doxycycline and marbofloxacin on in vitro biofilms of Staphylococcus pseudintermedius and Staphylococcus aureus. Exposure of biofilms for 15 hours to maximum concentrations of the antibiotics achievable in canine plasma only reduced biofilm bacteria by 0.5 to 2.0 log10 CFU, compared to the control, except for marbofloxacin which reduced S. aureus biofilms by 5.4 log10 CFU. Two-antibiotic combinations did not improve, and even decreased, bacterial killing. In comparison, 5 min-exposure to 2 % chlorhexidine reduced biofilms of the 2 tested strains by 4 log10 CFU. Our results showed that S. pseudintermedius biofilm, unlike S. aureus biofilm, was highly tolerant to all the drugs tested, consistent with the treatment failures observed in practice. Under our conditions, the use of topical chlorhexidine would probably be the best currently available strategy to reduce S. pseudintermedius biofilm.